The risk assessment of landslide hazards in the Badong section of Three Gorges using the variable fuzzy set theory - Li, Y.; Wang, Y. H.; Wu, Q. H.; Gu, X. B. (Frontiers in Physics, 2022)
The risk assessment of landslide hazards has tremendous influences on people's life and property safety, so its investigation is significant. The stratigraphic lithology, degree of weathering, the relationship between structural plane and slope direction, cohesive force, angle of internal friction, severe, average slope degree, the height of slope, and the type of landslide are selected as the risk assessment index of landslide hazards at first. Then the entropy weight-variable fuzzy sets model is introduced. Secondly, the relative membership degree matrix about the fuzzy variable sets is established, and the weight coefficients are determined based on the Entropy weight method. Finally, the risk level of landslide hazards is determined using the mean ranking feature value. The conclusions demonstrate that the results obtained based on the variable fuzzy sets method are consistent with the current specification; its accuracy arrives at 83%. Compared with the traditional way, its assessment process has higher reliability and efficiency. So it could provide a new alternative route to assess the risk level in civil engineering accurately.